Mentoring in a professional development program for novice teachers at a state university in Turkey: A qualitative inquiry - TOMAK, BURAK (My University, 2013)
In the last three decades, in teacher education, there has been a strong emphasis on the improvement of practice through reflective learning and teaching. This can be done either through individual study or with collaboration among teachers. In this context, the role of sociocultural learning in teacher education has also been explored (Johnson, 2009). For teachers to learn from one another, collaborative work is required. This study focused on the context of collaboration between novice teachers and experienced mentors as part of an In-service Training (INSET) program at a School of Foreign Languages in astate university located in Western Turkey. The purpose of the study was to explore the experiences of beginning novice teachers and investigate whether these teachers experienced professional development in connection with the collaboration with the experienced instructors. In this study, we also sought to understand whether the experienced teachers who acted as mentors of the novice teachers benefited from their engagement in the INSET program as mentors Four novice teachers and four experienced mentors participated in the study. All participants were interviewed to explore these teachers’ views on their professional development during the INSET program. Results revealed that neither the novice teachers nor experienced mentors considered major shifts in their teaching styles after participation in the professional development program. We found that two groups of participants had commenced the program with divergent interests. While the novice teachers expected to learn from their experienced mentors about how theories they had learned in their undergraduate programs could be applied in practice, the mentors anticipated that they could learn some new techniques and classroom activities from the novice teachers.
Keywords: teachereducation; INSET program; mentoring; noviceteachers; experiencedteachers